Indicators for assessing the impact of sectoral CO2 reduction in the industrial chain: Evidence from China. (August 2021) - Jia, Nanfei; Gao, Xiangyun; Liu, Donghui; Si, Jingjian; Jiang, Meihui
Highlights: Two new indicators are proposed to assess the impact of sector CO2 reduction on other sectors. These indicators consider the cascading effect between sectors in the industrial chain. Compared with existing indicators, new indicators can provide more information for policy. Electricity and hot water production and supply sector has a major impact on China's CO2 emissions. Abstract: To mitigate environmental pressure, many studies have calculated the CO2 emissions of a sector from the perspectives of production and consumption. However, determining a sector's CO2 reduction tasks based on these two indicators may underestimate the contribution of that sector to CO2 reductions in the entire economic system. The total CO2 emission reduction in the entire economic system cannot be regarded as a simple sum of CO2 emission reductions in various sectors. The situation that the reduction of CO2 emissions in one sector can promote the reduction of CO2 emissions in other sectors through a series of chain reactions in the industrial chain needs to be considered. Therefore, the purpose of this paper is to develop new indicators to assess the impact of sectoral CO2 reduction in the industrial chain, that is, when CO2 emissions are reduced in one sector, how much it promotes to the reductions in other sectors. We take China as a case and gain additional insights that are not available from existing indicators. The results reveal when the CO2 emissions of the Electricity and hot water production and supply sector change by 10%, its PCIC-CE and CCIC-CE are 4.13% and 3.83%, respectively. This indicate that the direct reduction of CO2 emissions in the sector has an additional impact on the CO2 emissions of the entire economic system. Hence, the new environmental indicators proposed in this paper can complement the existing indicators and guide sector-level environmental pressure mitigation strategies from a holistic perspective.